(untitled) (Analysis in Theory and Applications, 2014)
In this paper, we introduce the class of n-normed generalized difference sequences related to _p-space. Some properties of this sequence space like solidness, symmetricity, convergence-free etc. are studied. We obtain some inclusion relations involving this sequence space.